MEMPREDIKSI KESEHATAN BANK DENGAN RASIO CAMELS PADA BANK PERKREDITAN RAKYAT - Herry Laksito; Sutapa Sutapa (University of Merdeka Malang, 2010)
The Research was empirically retest analyses financial performance under CAMELSratios on degree of bank health. The research model was test financial statements underfinancial ratios on degree of bank health. The purpose of research was to analyze financialratios such as Capitals, Assets, Management, Earnings, Liquidity and sensitivity on degree ofbank health. The population was BPR residing in Pati Sub-Province. According to StatisticCenter Board on 2006, there were 68 BPR residing in Pati Sub-Province. Selection of samplesused purposive sampling with special characteristics suitable with research scopes. So, thesamples of research are 61 Bank Perkreditan Rakyat.Tools of analyses used Regression Logistic.The result of research was from all CAMELS ratios which effect on degree of bank health,Capital which was measured with CAR ratio had level of significance 0.011, Assets which wasmeasured with Assets utilization ratio had level of significance 0.022, Management whichwas measured with OPM ratio had level of significance 0.009, and Earning which was measuredwith ROE ratio had level of significance 0.009.